17th Conference on Great Lakes Research - Rukavina, N. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary Limnogeology continues to account for a significant part of the research reported in the annual Conferences on Great Lakes Research. At this year's meeting tie emphasis was on stratigraphie studies of post-glacial sediments, surface sediment geochemistry and shore processes. This is a reflection of current practical concerns with sediment loading, "cultural enrichment" of sediments and accelerated shore erosion.